Interatomic Coulombic decay following Ne 1s Auger decay in NeAr - Ouchi, Toshihiko; Sakai, K.; Fukuzawa, H.; Higuchi, I.; Demekhin, Philipp V.; Chiang, Ying-Chih; Stoychev, Spas Dimitrov; Kuleff, Alexander I.; Mazza, T.; Schöffler, M.; Nagaya, K.; Yao, M.; et al. (Physical review. A, Atomic, molecular, and optical physics, 2011)
Using momentum-resolved electron-ion multicoincidence spectroscopy, we have investigated interatomic Coulombic decay (ICD) in the heteronuclear NeAr dimer following Ne 1s Auger decay. The measured intensity ratio for the three ICD transitions Ne2+(2s−12p−11P)Ar to Ne2+(2p−21S)-Ar+(3p−1), Ne2+(2s−12p−11P)Ar to Ne2+(2p−21D)-Ar+(3p−1), and Ne2+(2s−12p−13P)Ar to Ne2+(2p−23P)-Ar+(3p−1) reasonably agree with predictions. The kinetic energy release distribution for the fragmentation to Ne2+(2p−21D)-Ar+(3p−1) after the ICD transition from singlet Ne2+(2s−12p−11P)Ar state, which is a mirror image of the kinetic energy distribution of the emitted ICD electrons, suggests that the corresponding ICD rate is roughly two times lower than predicted by ab initio calculations.
Gesehen am 19.10.2022